Infectivity and stability of hepatitis C virus in different perfusion solutions. Issue 5 (12th July 2019) - Helfritz, Fabian A.; Wanders, Verena; Bojkova, Denisa; Kuklinski, Nina; Westhaus, Sandra; Swoboda, Sandra; Minor, Thomas; Meuleman, Philip; Paul, Andreas; Steinmann, Eike; Ciesek, Sandra
Abstract: Background: Owing to organ shortage, transplantation of organs from HCV (hepatitis C virus) viremic donors into HCV negative individuals is getting more and more accepted. However, transmission of HCV to the host is nearly universal. Until now it is unknown if preservation solutions (PS) might alter infectivity and stability of HCV in the transplant setting. Therefore, seven different preservation solutions (PS) with variable composition were tested in vitro for their direct anti‐ and proviral effects on HCV. Methods: In vitro grown HCV based on the JFH‐1 isolate was used to characterize the effect of seven different PS on the HCV replication cycle including HCV attachment, entry, replication, and assembly. In addition, HCV stability in PS was tested. Results: Overall, 6/7 PS enhanced HCV infectivity: IGL‐1 increased HCV attachment and entry, UW Belzer and Perfadex boosted HCV entry. Production of novel viral particles was enhanced in HTK, UW Belzer, and IGL‐1. In contrast, viral replication was significantly reduced in HTK solution while all other PS had no effect on HCV RNA replication. HCV was significantly more stable in HTK solution. Euro Collins was the only PS that did not support HCV infectivity in cell culture. None of the used PS showed cytotoxic effects. Conclusion: Our data indicate that HCV infectivity and stability is maintained by several PS.